2018
DOI: 10.1177/0271121418763543
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Classroom Friendships: Teachers’ Confidence and Agreement With Children

Abstract: Over a century of research on peer relationships has revealed that friendships have a special role in young children's development of social competence and are distinctive from the contributions of adults or near-age relatives (Ladd, 2005). Close relationships with peers provide many opportunities for children to develop positive social behaviors, learn conflict-resolution skills, manage strong emotions, and contribute to their perceptions of self, such as self-concept and self-esteem (Ladd, 2005). Conversely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…More passive strategies such as allowing children to choose peers for specific activities or providing free choice opportunities are preferred, likely because teachers believe they should not interfere in children’s relationships (Hollingsworth & Buysse, 2009). Importantly, Meyer and Ostrosky (2018) reported moderate levels of agreement between teachers and young children regarding the identification of children’s friends, with decreased accuracy reported for children with disabilities. Relatedly, in a previous study with this dataset (Ferreira et al, 2017), we found that teachers’ reports on children’s sociometric status were weakly associated with sociometric status based on peer sociometric nominations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…More passive strategies such as allowing children to choose peers for specific activities or providing free choice opportunities are preferred, likely because teachers believe they should not interfere in children’s relationships (Hollingsworth & Buysse, 2009). Importantly, Meyer and Ostrosky (2018) reported moderate levels of agreement between teachers and young children regarding the identification of children’s friends, with decreased accuracy reported for children with disabilities. Relatedly, in a previous study with this dataset (Ferreira et al, 2017), we found that teachers’ reports on children’s sociometric status were weakly associated with sociometric status based on peer sociometric nominations.…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, our study does not add to the understanding of the social experiences of children with the most severe disabilities, who were either excluded based on sample selection criteria or could not participate or understand the sociometric tasks. Fifth, although we used a conventional and well-established measure of children’s friendships—one that captures the dyadic and reciprocal nature of children’s relationships and has been used with young children with disabilities (Meyer & Ostrosky, 2016; Yu et al, 2012)—we elicited children’s perspectives on preferred playmates, assuming enjoyment of joint play was a property of children’s friendships, but did not elicit children’s reports of their (best) friends explicitly (Meyer & Ostrosky, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Positive experiences such as friendships can provide a context for cooperation and negotiation ( Carter and Nutbrown, 2016 ) and ease children’s adjustment to school life ( Margetts, 2002 ; Corsaro, 2003 ; Peters, 2003 ). Meanwhile, negative peer experiences such as conflict or aggression can hinder children’s self-worth, social competence, and school engagement ( Kamper-DeMarco and Ostrov, 2019 ), leading to loneliness, depression, and school dropout ( Buhs et al, 2006 ; Meyer and Ostrosky, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research on teachers' accuracy (or diagnostic competence) in estimating the social inclusion of their students is fragmented and limited (Meyer and Ostrosky, 2018). Moreover, the terminology used to describe students' social situations is inconsistent (see Koster et al, 2009).…”
Section: What We Already Know About Teachers' Accuracy In Estimating mentioning
confidence: 99%
“…Another study by Liau et al (2004) found that teachers rated interpersonal violence in children less accurately when the children showed generally high levels of aggression. Similarly, a study comparing the ability of kindergarten teachers to identify friendships in children with and without disabilities (Meyer and Ostrosky, 2018) showed that the teachers performed less accurately for students with disabilities than for students without disabilities. Another finding also documents a lower rating accuracy of teachers in identifying peer relations of students with SEN (Shilshtein and Margalit, 2019): The correlation of children's self-reports and teachers' estimations of peer acceptance was lower in the group of students with learning disabilities than for those without SEN.…”
Section: Students' Senmentioning
confidence: 99%